A sodium-ion-interfacial positive electrode current collector and a preparation method thereof
Patent Information
- Application Number
- CN202611221174.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-13
AI Technical Summary
[0006]本发明的目的之一在于提供一种亲钠界面的无负极集流体,以解决无负极钠电池商用铝箔集流体亲钠性不足导致的钠沉积不均、界面副反应严重的问题
(1)本发明通过二氧化硅-炭黑复合涂层的原位界面反应,动态构建富含Na-Si-O与NaF的亲钠界面层,成核过电位可低至12mV,远低于纯铝箔与纯二氧化硅涂层,显著降低了钠沉积的能垒。同时,原位形成的富NaFSEI膜具有高离子电导率与高机械模量,可有效抑制界面副反应,提升无负极全电池的首次库仑效率,大幅减少活性钠的不可逆损耗,显著提升电池的循环稳定性。
Smart Images

Figure CN122907646A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of sodium-ion battery technology, specifically relating to a sodium-loving interface non-anode current collector and its preparation method. Background Technology
[0002] With the rapid development of new energy storage and electric vehicle industries, sodium-ion batteries have become an important technological route in the field of large-scale energy storage due to their advantages such as abundant sodium resources, low cost, and good compatibility with lithium-ion batteries. However, the energy density of traditional sodium-ion batteries with embedded anodes is relatively low, making it difficult to meet the requirements of high-energy-density scenarios. Sodium metal anodes are ideal anode materials for constructing high-energy-density sodium-based batteries, but conventional sodium metal batteries require the pre-filling of excess metallic sodium, which increases costs and safety risks, and also limits further improvements in energy density.
[0003] Electrodeless sodium metal batteries do not have a pre-installed sodium metal anode during assembly; instead, the current collector serves as the sodium deposition carrier. All active sodium originates from the cathode material, and sodium ions are deposited on the current collector surface during the first charge to form the sodium metal anode. This configuration eliminates the sodium metal preparation and assembly process, reducing costs and safety risks, and significantly improving battery energy density. However, the electrodeless system has extremely high requirements for the surface properties of the current collector. Commercial aluminum foil has low surface energy and poor sodium affinity, lacking active sites to induce uniform sodium nucleation, which easily leads to local preferential deposition, sodium dendrite growth, and exacerbated interfacial side reactions. Furthermore, the electrodeless system lacks excess sodium compensation, and the active sodium consumed by side reactions cannot be replenished, directly resulting in low initial coulombic efficiency and rapid capacity decay during cycles, severely restricting its practical application.
[0004] To improve the sodium affinity of current collectors, existing technologies mostly employ metal alloy coating modification strategies. Patent application CN117747847A discloses a sodium-affinity interface composite current collector, which uses dual-target magnetron sputtering to construct a sodium-affinity layer on the current collector surface with Cu, Fe, etc. as the matrix and dispersed Sb, Bi, and other alloy phases. Irreversible sodium alloying is used to improve cycle stability. However, this approach relies on magnetron sputtering equipment, which involves high equipment investment, slow coating rates, and is difficult to adapt to roll-to-roll mass production lines. Furthermore, the high cost of raw materials makes industrialization challenging. Patent application CN122025645A discloses a zinc-based sodium-affinity modified current collector, using zinc foil as the substrate. A Zn-Sb intermetallic phase modification layer is generated in situ through sputtering coating and annealing heat treatment, and uniform deposition is induced by reversible alloying. However, this solution uses zinc foil instead of traditional aluminum foil, which increases material cost and density, weakening the energy density advantage of the negative electrode-free battery. In addition, zinc has a low melting point and limited thermal stability. The preparation still requires magnetron sputtering and long-term annealing, resulting in a long process flow, high energy consumption, and low scalability.
[0005] In summary, existing technologies struggle to simultaneously achieve excellent electrochemical performance, low preparation costs, and good scalability. Therefore, developing novel sodium-loving current collector modification technologies is of great significance. Summary of the Invention
[0006] One of the objectives of this invention is to provide a sodium-loving interface current collector without a negative electrode, in order to solve the problems of uneven sodium deposition and severe interfacial side reactions caused by insufficient sodium affinity of commercial aluminum foil current collectors for sodium-free batteries.
[0007] The second objective of this invention is to provide a method for preparing a current collector without a negative electrode at a sodium-loving interface, which is used to prepare the aforementioned current collector without a negative electrode at a sodium-loving interface.
[0008] The objective of this invention can be achieved through the following technical solutions: In a first aspect, a sodium-loving interface non-negative current collector includes an aluminum foil substrate and a silica-carbon black composite conductive coating compounded on at least one surface of the aluminum foil substrate. The silica-carbon black composite conductive coating uses silica with a three-dimensional nanoporous network structure as the matrix framework, and carbon black conductive agent is uniformly dispersed inside the silica matrix, overlapping to form a continuous electronic conduction path, effectively overcoming the insulation defects of pure silica coating and reducing interfacial contact resistance.
[0009] The surface and inner walls of the pores of the silica-carbon black composite conductive coating are covered with a large number of silanol (Si-OH) polar groups. During the first charge-discharge cycle of the negative electrode-free sodium metal battery, the silanol groups can undergo in-situ interfacial chemical reactions with sodium salts and solvent molecules in the electrolyte, dynamically regulating the interfacial chemical environment and generating a sodium-loving interfacial layer rich in Na-Si-O species and NaF on the coating surface in situ.
[0010] The in-situ generated sodium-loving interface layer has a dual function: on the one hand, polar species such as Na-Si-O provide a large number of active sites that are conducive to uniform sodium nucleation, significantly reducing the nucleation overpotential of sodium deposition, guiding sodium metal to uniformly nucleate and grow on the coating surface, and effectively inhibiting the formation and growth of sodium dendrites; on the other hand, silanol groups can preferentially adsorb fluoride anions in the electrolyte and promote their decomposition, inducing the formation of a highly stable, high-modulus solid electrolyte interface film rich in NaF and silicate species, effectively blocking direct contact between the electrolyte and the deposited sodium metal, inhibiting the continuous occurrence of interfacial side reactions, and reducing the irreversible consumption of active sodium.
[0011] Furthermore, the thickness of the silica-carbon black composite conductive coating is 200 nm to 5 μm. If the coating thickness is too thin, a complete and continuous sodium-affinity interface cannot be formed, and the sodium-affinity modification effect is limited; if the coating thickness is too thick, the interface resistance and the overall thickness of the electrode will increase, reducing the battery energy density. Within the above thickness range, both the sodium-affinity modification effect and electrochemical impedance can be balanced.
[0012] Furthermore, the mass of the carbon black conductive agent is 30% to 70% of the theoretical mass of the silica matrix, preferably 50%. If the amount of carbon black added is too low, a continuous conductive path cannot be formed, and the improvement effect on interface resistance is not obvious; if the amount added is too high, it will destroy the three-dimensional network structure of silica, reduce the structural stability and silanol group content of the coating, and easily cause carbon black agglomeration, affecting the uniformity of the coating.
[0013] Furthermore, the aluminum foil substrate is a high-purity aluminum foil with a thickness of 12~15μm. High-purity aluminum foil has excellent conductivity and resistance to electrolyte corrosion, and is a conventional current collector substrate for negative electrode-less sodium batteries. This thickness range balances the mechanical strength of the current collector and the energy density of the battery.
[0014] Secondly, the present invention also provides a method for preparing the above-mentioned sodium-loving interface anode-free current collector, which is prepared by a sol-gel method combined with an dip-coating process, specifically including the following steps: (1) Substrate pretreatment: The aluminum foil substrate is degreased, alkali washed, acid washed, deionized water rinsed and nitrogen dried in sequence to remove surface oil, oxide layer and impurities, and obtain clean aluminum foil substrate.
[0015] Specifically, the degreasing treatment involves ultrasonically cleaning the aluminum foil in acetone for 5-10 minutes to remove surface oil; the alkaline washing involves immersing the aluminum foil in a 5wt% sodium hydroxide solution at 60°C for 3-5 minutes to remove the natural oxide layer and roughen the surface; the acid washing involves immersing the aluminum foil in a 10vol% dilute nitric acid solution for 2-3 minutes to neutralize the residual alkali and further clean the surface; finally, the aluminum foil is rinsed thoroughly with plenty of deionized water and dried with high-purity nitrogen for later use.
[0016] (2) Preparation of silica sol: Tetraethyl orthosilicate is used as the silicon source precursor, anhydrous ethanol is used as the co-solvent, deionized water is used as the hydrolysis reactant, and hydrochloric acid is used as the acid catalyst. After mixing in molar ratio, the mixture is stirred continuously at room temperature for 1-2 hours until a clear and transparent homogeneous silica sol is formed.
[0017] Preferably, the molar ratio of tetraethyl orthosilicate, anhydrous ethanol, deionized water, and hydrochloric acid is 1:(15-17):(3.5-4.5):(0.01-0.03). At this ratio, tetraethyl orthosilicate exhibits a moderate hydrolysis rate and good sol stability, forming a uniform three-dimensional network gel structure while avoiding sol aggregation and instability caused by excessively rapid hydrolysis.
[0018] (3) Preparation of carbon black suspension: Weigh carbon black conductive agent according to the design ratio, mix with an appropriate amount of anhydrous ethanol, add 5%~10% of dispersant by mass of carbon black, stir to initially disperse, and then perform ultrasonic dispersion treatment for 20~40 min to obtain a uniform and stable carbon black suspension.
[0019] The dispersant is polyvinylpyrrolidone or sodium dodecylbenzenesulfonate, which can effectively improve the dispersibility of carbon black in the ethanol system, inhibit the agglomeration of carbon black particles, and ensure the uniformity of the subsequent composite sol.
[0020] (4) Preparation of composite conductive sol: The carbon black suspension is slowly added dropwise to the silica sol under stirring. After the addition is completed, stirring is continued for at least 30 minutes to make the carbon black particles evenly distributed in the sol system. Then the mixed sol is transferred to a sealed container and aged at room temperature for 24~48 hours to obtain a silica-carbon black composite conductive sol with suitable viscosity and good stability.
[0021] The sealed aging process allows the hydrolysis and condensation reaction of tetraethyl orthosilicate to proceed fully, gradually increasing the viscosity of the sol and forming a suitable gel system for coating. At the same time, it promotes further compatibility between carbon black particles and the sol system, preventing phase separation during subsequent coating processes.
[0022] (5) Dipping and lifting coating: The pretreated aluminum foil substrate is vertically immersed into the aged composite conductive sol and kept fully submerged for 1 to 2 minutes to allow the sol to fully wet the surface of the aluminum foil. Then, the aluminum foil is vertically and uniformly lifted out of the liquid surface at a constant speed of 5 to 20 cm / min. After lifting, the aluminum foil coated with wet film is vertically suspended in a dust-free environment and left to stand for 10 to 20 minutes to allow the wet film to level and the solvent to evaporate initially.
[0023] The lifting speed is a key parameter for controlling coating thickness. The faster the speed, the more liquid is carried, and the thicker the coating; the slower the speed, the thinner the coating. The preferred lifting speed is 10~15cm / min, at which a coating with uniform thickness and few defects can be obtained.
[0024] (6) Drying and heat treatment: After standing, the coated aluminum foil is placed in a constant temperature drying oven and pre-dried at 80~100℃ for 1~2h to remove most of the solvent and moisture, so that the wet film is initially gelled; then the aluminum foil is transferred to a muffle furnace and heated to 300~500℃ at a heating rate of 1~5℃ / min, and held for 1~2h. After the holding is completed, the aluminum foil is naturally cooled to room temperature with the furnace, and finally a negative electrode current collector with a silica-carbon black composite conductive coating is obtained.
[0025] Slow heating rates prevent coating cracking caused by rapid evaporation of solvents and small molecules, ensuring the integrity of the coating structure. Medium-temperature heat treatment allows the gel to fully dehydrate and condense, forming a stable three-dimensional network structure. It also removes residual organic matter and dispersants without causing excessive densification of silica or destruction of the carbon black structure, thus balancing the conductivity and structural stability of the coating.
[0026] The beneficial effects of this invention are: (1) This invention dynamically constructs a sodium-rich interface layer containing Na-Si-O and NaF through in-situ interfacial reaction of a silica-carbon black composite coating. The nucleation overpotential can be as low as 12mV, which is much lower than that of pure aluminum foil and pure silica coating, significantly reducing the energy barrier for sodium deposition. At the same time, the in-situ formed NaF-rich SEI film has high ionic conductivity and high mechanical modulus, which can effectively suppress interfacial side reactions, improve the first coulombic efficiency of the electrodeless full cell, greatly reduce the irreversible loss of active sodium, and significantly improve the cycle stability of the battery.
[0027] (2) This invention is not a simple physical mixture of silica and carbon black, but rather achieves functional synergy between the two through sol-gel in-situ composite: carbon black is uniformly dispersed in the three-dimensional silica network, constructing a continuous conductive path, thus solving the inherent defects of poor insulation and high interfacial resistance of pure silica coatings; the silica framework provides stable support and anchoring for carbon black, inhibiting its agglomeration and shedding, while also playing a role in interface regulation and SEI construction due to its abundant silanol groups. The synergistic effect of the two achieves both high conductivity and strong sodium affinity, with a performance improvement far exceeding the simple superposition of single modification methods.
[0028] (3) Unlike the commonly used metal alloying sodium-affinity approach in existing technologies, this invention adopts an oxide-conductive agent composite system to construct a sodium-affinity interface based on in-situ interfacial chemical reactions. This avoids the volume expansion and structural pulverization problems during metal alloy cycling, resulting in better coating structural stability. At the same time, this technical route does not rely on expensive sodium-affinity metals and vacuum coating equipment, significantly reducing raw material and preparation costs compared to magnetron sputtering alloy coatings, thus possessing a differentiated technological competitive advantage.
[0029] (4) This invention uses a sol-gel method combined with an impregnation and pulling process. The equipment is simple and easy to operate. The raw materials are widely available and inexpensive. It can be directly adapted to existing roll-to-roll coating production lines in the battery industry, making it easy to achieve large-area, continuous, and large-scale production. At the same time, the heat treatment temperature is in the range of 300~500℃, which is highly compatible with the heat treatment process window of existing battery electrode preparation. No new special equipment is required, the industrialization cost is low, and it has significant prospects for industrial application.
[0030] (5) In response to the common industry problems of easy cracking of acidic sol-gel coatings and the impact of high temperature treatment on conductivity, this invention effectively alleviates the internal stress during coating drying and heat treatment by optimizing the precursor ratio, controlling the aging time, and adopting low-speed heating heat treatment through systematic process design, thereby reducing crack defects. At the same time, by precisely controlling the heat treatment temperature range, the destruction of carbon black microstructure is avoided while ensuring that the gel is fully cured, thus achieving a balance between coating density, adhesion and conductivity. Attached Figure Description
[0031] The invention will now be further described with reference to the accompanying drawings.
[0032] Figure 1 The image shows the overpotential curve of sodium deposition nucleation on a sodium-loving interface without a negative electrode current collector, prepared in Example 1 of this invention. Detailed Implementation
[0033] The specific embodiments of the present invention will be described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments.
[0034] In the following examples and comparative examples, all reagents used were commercially available analytical grade reagents, the aluminum foil was commercially available 12μm thick high-purity electronic aluminum foil, and the carbon black was commercially available superconducting carbon black.
[0035] Example 1 This embodiment prepares a sodium-loving interface current collector without a negative electrode. The specific steps are as follows: (1) Substrate pretreatment: Select high-purity aluminum foil with a thickness of 12 μm, cut it into appropriate size, and then perform ultrasonic cleaning with acetone for 8 min to degrease, immerse in 5 wt% sodium hydroxide solution at 60℃ for 4 min for alkaline washing, immerse in 10 vol% dilute nitric acid solution for 2 min for neutralization and acid washing, and finally rinse with a large amount of deionized water and blow dry with high-purity nitrogen to obtain clean aluminum foil substrate for use.
[0036] (2) Preparation of silica sol: The molar ratio of tetraethyl orthosilicate: anhydrous ethanol: deionized water: hydrochloric acid = 1:16:4:0.02 was used to mix the corresponding reagents. The mixture was placed on a magnetic stirrer and stirred at 300 rpm for 1.5 h at room temperature to obtain a clear and transparent homogeneous silica sol.
[0037] (3) Preparation of carbon black suspension: Weigh carbon black according to the theoretical mass of silicon dioxide generated by complete hydrolysis of tetraethyl orthosilicate, add an appropriate amount of anhydrous ethanol, and then add polyvinylpyrrolidone dispersant accounting for 8% of the carbon black mass. After stirring and mixing initially, ultrasonically disperse for 30 min to obtain a uniform and stable carbon black suspension.
[0038] (4) Preparation of composite conductive sol: Under continuous stirring, the carbon black suspension was slowly added to the silica sol at a rate of 2 mL / min. After the addition was completed, stirring was continued for 40 min to ensure that the carbon black was evenly dispersed in the sol. The mixed sol was then sealed and aged at room temperature for 36 h to obtain silica-carbon black composite conductive sol.
[0039] (5) Dipping and lifting coating: Using a dip-lifting machine, the pretreated aluminum foil is vertically immersed into the composite sol. After being completely immersed for 1.5 min, it is vertically and uniformly lifted at a constant speed of 10 cm / min to obtain the aluminum foil coated with a wet film. After lifting, the aluminum foil is vertically suspended in a dust-free and ventilated place for 15 min to allow the wet film to level naturally and the solvent to evaporate initially.
[0040] (6) Drying and heat treatment: The aluminum foil after standing was placed in a constant temperature drying oven and pre-dried at 90 °C for 1.5 h; then it was transferred to a muffle furnace and heated to 450 °C at a heating rate of 3 °C / min and held for 1.5 h. After the holding period, it was naturally cooled to room temperature with the furnace to obtain a silica-carbon black composite coating without a negative electrode current collector. The coating thickness was tested to be 300 nm.
[0041] Example 2 The preparation steps of this embodiment are basically the same as those of Example 1, except that in step (3), the amount of carbon black added is 30% of the theoretical mass of silicon dioxide generated by the hydrolysis of tetraethyl orthosilicate.
[0042] Example 3 The preparation steps of this embodiment are basically the same as those of Example 1, except that in step (3), the amount of carbon black added is 70% of the theoretical mass of silicon dioxide generated by the hydrolysis of tetraethyl orthosilicate.
[0043] Example 4 The preparation steps in this embodiment are basically the same as those in Example 1, except that in step (5), the dipping and lifting speed is 5 cm / min. The resulting coating thickness was measured to be 500 nm.
[0044] Example 5 The preparation steps in this embodiment are basically the same as those in Example 1, except that in step (5), the dipping and lifting speed is 20 cm / min. The resulting coating thickness was measured to be 150 nm.
[0045] Example 6 The preparation steps of this embodiment are basically the same as those of Example 1, except that in step (6), the maximum temperature of heat treatment is 350 °C and the holding time is still 1.5 h.
[0046] Example 7 The preparation steps of this embodiment are basically the same as those of Example 1, except that in step (6), the maximum temperature of heat treatment is 550 °C and the holding time is still 1.5 h.
[0047] Comparative Example 1 This comparative example prepared a pure silica-coated current collector without a negative electrode, forming a single-variable control with Example 1. The specific steps are as follows: (1) Substrate pretreatment: exactly the same as step (1) in Example 1.
[0048] (2) Preparation of silica sol: exactly the same as step (2) in Example 1.
[0049] (3) Sol aging: Seal the silica sol and age it at room temperature for 36 h.
[0050] (4) Dipping and lifting coating: exactly the same as step (5) in Example 1, with a lifting speed of 10 cm / min.
[0051] (5) Drying and heat treatment: exactly the same as step (6) in Example 1, keep at 450 ℃ for 1.5 h, cool with furnace to obtain pure silicon dioxide coated negative electrode current collector.
[0052] Comparative Example 2 This comparative example uses blank high-purity aluminum foil without any coating modification as the negative electrode current collector. The pretreatment steps are the same as step (1) of Example 1, without subsequent coating treatment, and it serves as a blank control group.
[0053] Comparative Example 3 The specific steps for preparing pure carbon black coated aluminum foil in this comparative example are as follows: Carbon black and polyvinylidene fluoride binder were mixed at a mass ratio of 9:1, and N-methylpyrrolidone solvent was added and stirred to form a uniform slurry. The slurry was then coated onto the surface of pretreated aluminum foil using a doctor blade coating method and dried under vacuum at 90 °C for 12 h to obtain a pure carbon black coated aluminum foil. The coating thickness was controlled to be 300 nm, which is comparable to the coating thickness in Example 1.
[0054] Comparative Example 4 The specific steps for preparing physically mixed silica-carbon black coated aluminum foil in this comparative example are as follows: Fumed silica powder and carbon black were mixed at a mass ratio of 1:0.5. Polyvinylidene fluoride binder accounting for 10% of the total powder mass and an appropriate amount of N-methylpyrrolidone solvent were added. The mixture was stirred at high speed to form a uniform slurry. The slurry was then coated onto the surface of pretreated aluminum foil with a doctor blade and dried under vacuum at 90 °C for 12 h to obtain a physically mixed coated aluminum foil. The coating thickness was controlled to be 300 nm, which is comparable to the coating thickness in Example 1.
[0055] Battery assembly and performance testing Using the current collectors prepared in the above embodiments and comparative examples as negative electrode current collectors, sodium metal coin cells without negative electrodes were assembled and their electrochemical performance was tested.
[0056] Testing standards are based on the following: This performance test refers to the general testing principles for battery charge and discharge cycles in GB / T31484-2015 "Requirements and Test Methods for Cycle Life of Power Batteries for Electric Vehicles". The test procedure is formulated by combining the test specifications of button cells and the structural characteristics of sodium metal batteries without negative electrodes. The nucleation overpotential test adopts the constant current charging potential change method commonly used in the field of electrochemistry. The first coulombic efficiency and cycle performance test follows the industry-standard specifications for electrochemical performance testing of sodium-ion batteries.
[0057] The specific testing process is as follows: Preparation of positive electrode sheet: Sodium vanadium fluorophosphate is used as the positive electrode active material, conductive carbon black is used as the conductive agent, and polyvinylidene fluoride is used as the binder. The materials are weighed at a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone solvent is added. The mixture is stirred at high speed to form a uniform positive electrode slurry. The slurry is uniformly coated on the surface of a 12μm thick aluminum foil, dried under vacuum at 120℃ for 12h, rolled to a suitable compaction density, and cut into circular positive electrode sheets with a diameter of 12mm. The positive electrode active material loading is 10mg / cm².
[0058] Battery Assembly: Assembly was performed using a CR2032 coin cell battery casing in an argon-filled glove box (water and oxygen content both below 1 ppm). The positive electrode shell, positive electrode plate, glass fiber separator, electrolyte, negative electrode current collector, gasket, spring contact, and negative electrode shell were stacked sequentially, then compacted and sealed to obtain a sodium metal battery without a negative electrode. The electrolyte used was a 1 mol / L sodium hexafluorophosphate solution in ethylene glycol dimethyl ether.
[0059] Performance testing: (1) Nucleation overpotential test: The Blue Battery test system was used to charge the battery at a constant current density of 0.1C. The voltage plateau at the beginning of charging was recorded. The sodium deposition nucleation overpotential was the difference between the initial voltage drop and the current density.
[0060] (2) Initial charge-discharge and coulombic efficiency test: Charge to 4.0V with a constant current of 0.1C, let stand for 5 min, and then discharge to 1.5V with a constant current of 0.1C. Record the initial charge specific capacity and discharge specific capacity, and calculate the initial coulombic efficiency.
[0061] (3) Cyclic performance test: After the first charge and discharge at 0.1C rate, constant current charge and discharge cycle test is performed at 0.5C rate in the voltage range of 1.5~4.0V, and the discharge capacity retention rate after 100 cycles is recorded.
[0062] The results are shown in Table 1: Table 1
[0063] As shown in Table 1, comparing Example 1 and Comparative Example 1, under the same sol-gel system and preparation process, the nucleation overpotential of the composite coating with 50% carbon black added decreased from 30 mV to 12 mV; the initial coulombic efficiency increased from 68% to 89%; and the capacity retention after 100 cycles increased from 47.3% to 82.3%. The nucleation overpotential test results are as follows: Figure 1 As shown, the current collector in Example 1 exhibits a significant voltage drop during the initial stage of sodium deposition, corresponding to the sodium metal nucleation process. Its nucleation overpotential is 12mV, far lower than that of the blank aluminum foil and the pure silica coating, demonstrating the excellent sodium-affinity modification effect of the composite coating of this invention. The core reason for the performance improvement lies in the continuous conductive pathway constructed by carbon black within the silica network, fundamentally solving the defects of poor insulation and high interfacial resistance in the pure silica coating. This allows the sodium-affinity sites of the silanol groups on the silica surface to function effectively, achieving a balance between conductivity and sodium affinity through synergy.
[0064] Comparing Example 1 with Comparative Examples 3 and 4, it can be seen that the pure carbon black coating can only slightly reduce the nucleation overpotential, with an initial coulombic efficiency of only 26%, indicating that pure carbon black does not have the ability to regulate the sodium-loving interface and cannot effectively improve interface stability. The physically mixed silica-carbon black coating performs slightly better than pure silica, but the nucleation overpotential still reaches 25mV and the initial efficiency is only 70%, which is far lower than that of Example 1, which uses the in-situ composite method of this invention. This result proves that the in-situ composite of silica and carbon black achieved by the sol-gel method in this invention is not a simple superposition of their functions, but rather forms a synergistic effect: the three-dimensional network of in-situ grown silica ensures the uniform distribution and high activity of silanol groups, while anchoring carbon black particles to form a uniform and continuous conductive path. The two work together to achieve a balance between low nucleation overpotential and high initial efficiency.
[0065] Comparing Examples 1, 2, and 3, it can be seen that significant performance improvement can be achieved within the range of 30% to 70% carbon black addition, with 50% being the optimal ratio. If the addition amount is too low, the conductive path will be discontinuous, and the improvement in interface resistance will be limited. If the addition amount is too high, the silica network structure will be destroyed, the sodium-affinity sites will be reduced, and the performance will actually decrease.
[0066] Comparing Examples 1, 4, and 5, it can be seen that the lifting speed directly determines the coating thickness. Lifting speeds of 5 to 20 cm / min can all achieve effective modification effects, with 10 cm / min being the optimal speed. If the coating is too thick, it will increase the interfacial resistance; if it is too thin, a complete sodium-loving interface cannot be formed.
[0067] Comparing Examples 1, 6, and 7, it can be seen that a satisfactory modification effect can be obtained in the heat treatment temperature range of 300~500℃, with 450℃ being the optimal temperature. If the temperature is too low, the gel will not be fully cured and there will be more residual organic matter. If the temperature is too high, the silanol groups will be destroyed and the silica will be over-densified, both of which will lead to a decrease in performance.
[0068] Compared with the blank aluminum foil of Comparative Example 2, the nucleation overpotential of the optimal embodiment of the present invention is reduced by 76.5%, the first coulombic efficiency is improved by more than 7 times, and the cycle capacity retention rate is improved by nearly 2 times. The performance improvement is extremely significant, which fully proves the effectiveness of the technical solution of the present invention.
[0069] The above-disclosed embodiments are merely a few specific examples of the present invention. However, the embodiments of the present invention are not limited thereto, and any variations that can be conceived by those skilled in the art should fall within the protection scope of the present invention.
Claims
1. A sodium-loving interface-free current collector, characterized in that, Includes an aluminum foil substrate and a silica-carbon black composite conductive coating laminated on at least one surface of the aluminum foil substrate; The silica-carbon black composite conductive coating includes a silica matrix with a three-dimensional nanoporous network structure and a carbon black conductive agent uniformly dispersed in the silica matrix, wherein the carbon black forms a continuous electronic conduction pathway inside the coating. The surface of the silica-carbon black composite conductive coating is distributed with silanol groups. These silanol groups are used to react in situ with the electrolyte and sodium salt during the first charge-discharge cycle of the negative electrode-free sodium metal battery, dynamically generating a sodium-loving interface layer rich in Na-Si-O species and NaF on the coating surface.
2. The sodium-loving interface current collector without a negative electrode according to claim 1, characterized in that, The thickness of the silica-carbon black composite conductive coating is 200 nm to 5 μm.
3. The sodium-loving interface current collector without a negative electrode according to claim 1, characterized in that, The mass of the carbon black conductive agent is 30% to 70% of the theoretical mass of the silica matrix.
4. The sodium-loving interface current collector without a negative electrode according to claim 1, characterized in that, The aluminum foil substrate is a high-purity aluminum foil with a thickness of 12~15μm.
5. A method for preparing a sodium-loving interface-free current collector according to any one of claims 1 to 4, characterized in that, Includes the following steps: (1) Substrate pretreatment: The aluminum foil substrate is degreased, alkali washed, acid washed, rinsed and dried in sequence to obtain a clean aluminum foil substrate; (2) Preparation of silica sol: Tetraethyl orthosilicate is used as the silicon source precursor, anhydrous ethanol is used as the co-solvent, deionized water is used as the hydrolysis reactant, and hydrochloric acid is used as the acid catalyst. The mixture is stirred at room temperature until a clear and transparent homogeneous sol is formed, namely silica sol. (3) Preparation of carbon black suspension: Carbon black conductive agent is mixed with anhydrous ethanol, dispersant is added, and a stable carbon black suspension is obtained by ultrasonic dispersion treatment; (4) Preparation of composite conductive sol: The carbon black suspension is slowly added dropwise to the silica sol and stirred continuously until the carbon black is uniformly dispersed. Then it is sealed and aged to obtain silica-carbon black composite conductive sol; (5) Immersion and lifting coating: The clean aluminum foil substrate is vertically immersed into the composite conductive sol, and after immersion, it is vertically lifted at a constant speed to obtain an aluminum foil coated with a wet film. (6) Drying and heat treatment: The aluminum foil coated with wet film is first pre-dried, then subjected to programmed heating heat treatment, and after heat preservation, it is naturally cooled with the furnace to obtain the sodium-loving interface non-negative electrode current collector.
6. The method for preparing a sodium-loving interface current collector without a negative electrode according to claim 5, characterized in that, In step (2), the molar ratio of tetraethyl orthosilicate, anhydrous ethanol, deionized water and hydrochloric acid is 1:(15-17):(3.5-4.5):(0.01-0.03), and the stirring time at room temperature is 1-2 hours.
7. The method for preparing a sodium-loving interface current collector without a negative electrode according to claim 5, characterized in that, In step (3), the dispersant is polyvinylpyrrolidone or sodium dodecylbenzenesulfonate, and the amount of dispersant added is 5% to 10% of the mass of the carbon black conductive agent; the ultrasonic dispersion time is 20 to 40 min.
8. The method for preparing a sodium-loving interface-free current collector according to claim 5, characterized in that, In step (4), the sealing and aging time is 24~48h, and the aging temperature is room temperature.
9. The method for preparing a sodium-loving interface current collector without a negative electrode according to claim 5, characterized in that, In step (5), the aluminum foil is fully immersed in the sol for 1 to 2 minutes, and the lifting speed is 5 to 20 cm / min.
10. The method for preparing a sodium-loving interface current collector without a negative electrode according to claim 5, characterized in that, In step (6), the pre-drying temperature is 80~100℃ and the time is 1~2h; the heating rate of the heat treatment is 1~5℃ / min, the heat treatment temperature is 300~500℃, and the holding time is 1~2h. In step (1), the degreasing is ultrasonic cleaning with acetone, the alkaline washing is treatment with 5wt% sodium hydroxide solution at 60°C, and the acid washing is neutralization treatment with 10vol% dilute nitric acid solution.
Citation Information
Patent Citations
Composite current collector with sodium-philic interface, preparation of composite current collector and application of composite current collector in negative-electrode-free sodium battery
CN117747847A
Zinc-based sodium-philic modified current collector, preparation method thereof and negative-electrode-free sodium metal battery
CN122025645A